Bangladesh : Development Forum Economic Update - World Bank (Washington, DC, 2013)
The report reviews recent economic developments, showing economic growth continues to its path, and, aided by global economic recovery, export growth remains strong. The forex market has been stable since the national currency (taka) was floated in by the end-May 2003. The fiscal stance for FY04 remains expansionary, but within prudent limits, and without straining fiscal sustainability, whereas the monetary policy stance - tightened considerably last summer to facilitate exchange rate liberalization - is becoming increasingly adaptable, in recognition of the favorable macro-financial conditions, seemingly on a prudent course. Higher growth in the 1990s also translated into sharper declines in income poverty. Notwithstanding the impressive gains thus far, the magnitude of remaining development challenges is enormous. In June 2003, the Government adopted its first ever medium-term macroeconomic framework, which underpins its poverty reduction strategy, and should contribute to high growth, and fast-paced poverty reduction. The path of the fiscal policy in the medium-term framework, is consistent with Bangladesh's reform needs, and public debt sustainability. And, despite recent deterioration, the public debt stock appears sustainable. However, Bangladesh remains vulnerable to the scheduled phase out of the Multi-Fiber Arrangement (MFA) quotas from January 2005. The report estimates GDP growth rates would be needed if the stated poverty reduction objectives are to be achieved, and, analytical work suggests that higher growth is likely to come mainly from productivity increases. Regarding the agenda for human development it is indicated that with good foundations already built, Bangladesh should now move swiftly with the second generation reforms needed to further improve human development. These entail complementing increased social spending with significant improvements in the institutional framework for service delivery, as specified in the Interim Poverty Reduction Strategy Paper, with increased efforts to promote decentralization.